(untitled) (Bangladesh Journal of Medical Education, 2021)
This descriptive type of cross-sectional study was conducted with an objective to find out the present employment and academic status of recent dental graduates in Dhaka city. The study was conducted for one year from July 2019 to June 2020 at different work places of recent dental graduates and residence of unemployed dental graduates in Dhaka city. A total of 414 recent dental graduates were the respondents of the study. Study revealed that 212 (51.2%) of the respondents were male and 202 (48.8%) of the respondents were female. With regards to employment, it was revealed that 340 (82.1%) of the respondents were employed as dental surgeon and 57 (13.8%) of the respondents were yet to get formal employment. Among the employed dental graduates, 203 (57%) were full-time employee and 154 (47%) were part-time. Only 55 (15.4%) dental surgeons among them were working in government sector and rest were non-government employee or self-employed. Self-employment as a dental surgeon was the main source of income for 179 (43.2%) of total respondents. Regarding the job satisfaction, 139 (33.6%) were moderately satisfied and 182 (44%) were not satisfied with their pay standard. With regards to further academic engagement, 88 (21.2%) respondents were enrolled in different postgraduation courses whereas 205 (49.5%) of the respondents were also engaged in learning activities to get admitted into postgraduation courses. Study recommended that newly graduated dental surgeons could be utilized by engaging into both urban and rural areas by creating scope in both government and nongovernment sectors. Further academic engagement may be ensured by initiating new courses of dentistry and by increasing number of affiliated institutes for post-graduation. Bangladesh Journal of Medical Education Vol.12(2) July 2021: 10-17